Fixed Point Theorems for Weakly Generalized w-Contraction Mappings and Applications - M. Menaka; M. Marudai (International Journal of Mathematics And its Applications, 2018)
In this paper, we prove fixed point theorems for weakly generalized w-contraction mappings in the setting of w-distances which generalize results of Wongyat and Sintunavarat [16]. As an application, we obtain the existence and uniqueness solutions for nonlinear Fredholm and Volterra integral equations.